Influence of Non-Contact-Based Spiritual Blessing Energy Treatment on Growth Metrics and Reproductive Productivity in Okra (Abelmoschus esculentus L.) - Kumar Trivedi, Mahendra; Rajendra Phutankar, Nikhil; Bapu Gaikwad, Tejas; Dattaram Kadam, Vivek; Mondal, Sambhu; Jana, Snehasis (Journal of Farming, 2026)
This study investigated the influence of a non-contact based spiritual blessing energy treatment (SBET) on the growth dynamics and reproductive productivity of okra (Abelmoschus esculentus L.). Utilizing a Randomized Complete Block Design, okra seeds and farming land were divided into treated and untreated cohorts under identical environmental conditions. The treated cohort received spiritual thought-intention-based energetic blessings, while the control group received none (untreated). Both qualitative and quantitative analysis revealed significant enhancements in the treatment group across multiple agronomic indices. Phenological parameters such as plant height, stem collar diameter, number of branches per plant, number of leaves per plant, fruit weight, fruit length, and fruit diameter were significantly increased by 29.57% (p ≤ 0.001), 45.83% (p ≤ 0.001), 40.49% (p = 0.006), 41.61% (p ≤ 0.001), 47.61% (p ≤ 0.001), 40.26% (p ≤ 0.001), and 37.58% (p ≤ 0.001), respectively, in the treatment group compared to the control group. Further, fruits yield (tons per hectare) was rose by 38.25% in the treatment group compared to the control. These findings suggest that subtle, thought-intention-based spiritual blessing energy treatment may interact positively with plant biophysical pathways, modifying cellular or metabolic efficiency and improved vegetative growth and yields of okra.
Keywords: okra; spiritual blessing; prayer; biofield treatment; morphology; phenology; yield